2004
DOI: 10.1128/jvi.78.12.6666-6675.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Population Genetics of Cucumber Mosaic Virus in California: Evidence for Founder Effects and Reassortment

Abstract: The structure and genetic diversity of a California Cucumber mosaic virus (CMV) population was assessed by single-strand conformation polymorphism and nucleotide sequence analyses of genomic regions 2b, CP, MP, and the 3 nontranslated region of RNA3. The California CMV population exhibited low genetic diversity and was composed of one to three predominant haplotypes and a large number of minor haplotypes for specific genomic regions. Extremely low diversity and close evolutionary relationships among isolates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
71
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 41 publications
13
71
2
1
Order By: Relevance
“…3). showed that reassortment occurs at rather low rates in viruses of the family Bunyaviridae (Henderson et al, 1995;Nemirov et al, 1999) or of other families (Fraile et al, 1997;Lin et al, 2004;Roossinck, 2002;Bonnet et al, 2005;Miranda et al, 2000;Iturriza-Gó mara et al, 2001;Watanabe et al, 2001;McDonald et al, 2009), which could be due to strong selection acting against reassortants (Brown et al, 2002;Fraile et al, 1997;Escriu et al, 2007). Some viral taxa seem however to show more extensive reassortment (Silander et al, 2005;Lindstrom et al, 2004;Nelson et al, 2008;Khiabanian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3). showed that reassortment occurs at rather low rates in viruses of the family Bunyaviridae (Henderson et al, 1995;Nemirov et al, 1999) or of other families (Fraile et al, 1997;Lin et al, 2004;Roossinck, 2002;Bonnet et al, 2005;Miranda et al, 2000;Iturriza-Gó mara et al, 2001;Watanabe et al, 2001;McDonald et al, 2009), which could be due to strong selection acting against reassortants (Brown et al, 2002;Fraile et al, 1997;Escriu et al, 2007). Some viral taxa seem however to show more extensive reassortment (Silander et al, 2005;Lindstrom et al, 2004;Nelson et al, 2008;Khiabanian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest it is also that, among our five isolates, Ab (originated from weed A. theophrasti) showed the highest nucleotide sequence variation in comparison with other isolates. Based on our results, there was no correlation between CP gene sequence variation and geographical origin or original host plant, as described before (Hayakawa et al 1989;Lin et al 2004). To our knowledge, this is the first report of CMV infection of A. theophrasti in the world.…”
Section: Discussionmentioning
confidence: 96%
“…Coat protein gene of CMV isolates was amplified by immunocapture RT-PCR protocol (Nolasco et al 1993), using F4 (forward) 5'-TTGAGTCGAGTCATG-GACAAATC-3'/F3 (reverse) 5'-AACACGGAATCA-GACTGGGAG-3' primer pair designed by Lin et al (2004). Briefly, fresh leaf tissue of N. tabacum plant, infected with each CMV isolate, was macerated in PBST buffer containing 2% PVP and incubated overnight at 4°C in PCR vials which had been coated with CMV IgG before.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that selection against heterologous gen combinations increases as host colonization progresses along the infection cycle of Cucumber mosaic virus [32], affecting the frequency of genetic exchange. This explains that recombinants and reassortants are often found at low frequencies [33,34], although the frequency of particular combinations may be dependent on agro-ecological factors [17,19], and support the hypothesis of co-adaptation of gene complexes within the viral genomes [32,35].…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcmentioning
confidence: 88%